Intensive monitoring and interpersonal counselling by lady health worker improves the coverage of vitamin A among children between ages 6 and 59 months in selected low performing provinces of Pakistan - Janjua, Tausif Akhtar; Nawaz, Khalid; Chaudhery, Deepika Nayar; Kaushik, S.; Raut, Manoj Kumar (International Journal Of Community Medicine And Public Health, 2018)
Background: Nutrition International, previously known as Micronutrient Initiative, has been supporting the government of Pakistan to address vitamin A deficiency in 24 districts of Balochistan and Khyber Pakhtunkhwa and 78 union councils of Lahore and Karachi. The program aims to improve capacity of health managers and frontline workers on supply chain management and monitoring; monitoring of stock-outs at health facilities and frontline distribution points; and focus on regular monitoring and supervision through EPI and health departments. Challenge however remains in achieving meaningful coverage. The Nutrition International piloted an intensive monitoring strategy in a sub-set of four districts of Balochistan and KPK and 14 union councils in Karachi and Lahore with an aim to improve coverage of vitamin A. The study assessed the changes in coverage of vitamin A supplementation 2011 to 2012 due to the intensive monitoring. Methods: Two rounds of repeated cross-sectional mixed-methods surveys were conducted on a sample of 2,579 and 2,580 caregivers during baseline and end-line respectively. Low performing districts identified in each of the four provinces constituted the study domain. The sample of households in each region was selected using a two stage cluster sampling strategy. Results: The coverage of Vitamin A registered an absolute increase of 35.7 percent points in the intensive monitoring districts compared to the other districts, where it was 29.6 percent points in the end-line over the baseline. Conclusions: It was observed that intensive monitoring and interpersonal counselling by lady health worker is instrumental in improving the coverage of Vitamin A in certain programmatic settings in Pakistan.